Local engagement of Chinese international students in host societies: a perspective of diasporic Chinese community building (CCB) in the UK - Wu, Bin (World Scientific Publishing, 2016)
Social changes in diasporic Chinese communities in the 21st century calls for a new approach to understand new dynamics, resources and opportunities to bring together all stakeholders, both Chinese and non-Chinese, toward mutual trust, effective communication and collaboration in host countries (Wu, 2010; 2011). For this purpose, this paper aims to develop a framework for the process of diasporic Chinese community building (CCB) in general and for the local engagement of Chinese international students in the UK in particular. Research questions include: To what extents can Chinese students be viewed as part of diasporic Chinese communities? By what channels can they be interconnected with the wider society? Where are resources, interfaces and barriers against their participations and contribution to the CCB? Based upon a questionnaire survey in Nottingham, four types of social networking among Chinese students are identified, and the relationships with their behaviours in community engagement and implications for the CCB are discussed.